Processing and in vitro bioactivity of a β-Ca3(PO4)2-CaMg(SiO3)2 ceramic with the eutectic composition (2016)
In this study, a dense bioactive ceramic, with nominal composition (wt.%) 40 Ca3(PO4)2–60 CaMg(SiO3)2, was prepared by solid state sintering of homogeneous compacted mixtures of fine synthetic Ca3(PO4)2 and CaMg(SiO3)2 powders. The results obtained by X-ray diffraction and field emission scanning electron microscopy with microanalysis indicate that the ceramic composite showed a fine grained and homogeneous microstructure consisting of diopside (CaMg(SiO3)2) and whitlockite (-Ca3(PO4)2ss) grains with very small amounts of apatite. The flexural strength and elastic modulus values of the composite are similar to those of cortical human bone. Bioactivity was experimentally evaluated by examining in vitro apatite formation in simulated body fluid (SBF). In addition, a simulation of the dissolution properties of the different phases present in the material in SBF was carried out by thermodynamic calculations, with the purpose of understanding the in vitro results obtained. The experimental results demonstrated that, during soaking in SBF, the grains of whitlockite dissolved preferentially than those of diopside, leaving a porous surface layer rich in diopside. Subsequently, partial dissolution of the remaining diopside occurred and the porous surface of the ceramic became coated by a bone-like apatite layer after 7 days in SBF. This bioceramic containing -Ca3(PO4)2 and CaMg(SiO3)2 is expected to be useful to fabricate scaffolds for bone repair